Safety, feasibility, acceptability and effects of a behaviour-change intervention to change physical activity behaviour among people with multiple sclerosis: Results from the iStep-MS randomised controlled trial. (December 2020) - Ryan, Jennifer M; Fortune, Jennifer; Stennett, Andrea; Kilbride, Cherry; Lavelle, Grace; Hendrie, Wendy; DeSouza, Lorraine; Abdul, Mohammed; Brewin, Debbie; David, Lee; Anokye, Nana; Victor, Christina; et al.
Background: There is limited information regarding the safety, feasibility and acceptability of behaviour-change interventions to increase physical activity (PA) and reduce sedentary behaviour among people with multiple sclerosis (MS). Prior to evaluating efficacy, it is important to identify problems with feasibility and acceptability, which may undermine effectiveness. Objective: To examine the safety, feasibility and acceptability of a behaviour-change intervention to increase PA and reduce sedentary behaviour among people with MS. Methods: Sixty people received a 3-month intervention or usual care. Fatigue, pain and adverse events (AEs) were assessed. Feasibility and acceptability were explored through focus groups with physiotherapists and interviews with participants. Fidelity to intervention content, delivery skills, programme receipt and programme task were assessed. Results: There was no difference in AE rate between groups ( p = 0.965). Fatigue and pain were not higher in the intervention group at 3 or 9 months. Therapists reported the intervention was feasible to deliver and fidelity was acceptable. Twenty-nine participants (97%) attended at least 75% of sessions. Participants found the intervention acceptable but suggested some amendments were required to intervention components. Conclusions: The intervention was safe, feasible and acceptable. Although modifications are required to intervention components, the intervention warrants further evaluation in a future trial.